دور الدولة القائد في التكامل الاقليمي قراءة في تجربة جماعة التنمية لدول الجنوب الافريقي SADC - عـطيـــة, إدريـــس (revue mofakir, 2018)
The study seeks exposure to form an integral is of the leading models Integrative successful at African and global, and represent it in the reading experience SADC from except for oncoming role in foreign policy, and the extent of its effectiveness in analyzing behaviors countries in its regional, and especially when it comes to the role of the state-level integrative Bearing this state has a responsibility to manage the integration process, and the trend towards interoperability through solidarity conduct crises territory, and work to develop the rules of collective action, as well as the activation of fusion programs. South Africa is now the most prominent state in South Africa, qualified mainly because to play the lead role, due to the elements of its national power, and envisioned for her role . الملخص : تستهدف الدراسة التعرض لنموذج تكاملي يعتبر من أبرز النماذج التكاملية الناجحة على الصعيد الإفريقي والعالمي، وتمثًل ذلك في قراءة لتجربة ' السادك ' SADC من خلا ل مقترب الدور في السياسة الخارجية، ومدى نجاعته في تحليل سلوكات الدول في محيطها الإقليمي، وبخاصة إذا تعلق الأمر بدور الدولة على الصعيد التكاملي، إذ تضع هذه الدولة على عاتقها مسؤولية إدارة العملية التكاملية، والاتجاه بها نحو التضامن البيني من خلال تسيير أزمات الإقليم، والعمل على تطوير قواعد العمل الجماعي، وكذا تفعيل البرامج الاندماجية . وتعد جنوب إفريقيا الدولة الأبرز في إفريقيا الجنوبية، والمؤهلة أساسا لأن تضطلع بدور الدولة القائدة في المنطقة، ويرجع ذلك إلى مقومات قوتها القومية، ومجال تصورتها عن دورها في محيطها الإقليمي المباشر كمجال حيوي .